2018
DOI: 10.1002/psp4.12309
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacometabolomics Informs About Pharmacokinetic Profile of Methylphenidate

Abstract: Carboxylesterase 1 (CES1) metabolizes methylphenidate and other drugs. CES1 gene variation only partially explains pharmacokinetic (PK) variability. Biomarkers predicting the PKs of drugs metabolized by CES1 are needed. We identified lipids in plasma from 44 healthy subjects that correlated with CES1 activity as determined by PK parameters of methylphenidate including a ceramide (q value = 0.001) and a phosphatidylcholine (q value = 0.005). Carriers of the CES1 143E allele had decreased methylphenidate metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…CES1 is involved in drug detoxification and metabolism of endogenous metabolites, including cholesterol and triglycerides ( Redinbo et al., 2003 ). Interestingly, docking studies revealed that BAs can bind the catalytic site of CES1, with CDCA and TCA having the strongest binding activity ( Kaddurah-Daouk et al., 2018 ). Further mechanistic studies will be required to gain further insight into this CES1-BA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…CES1 is involved in drug detoxification and metabolism of endogenous metabolites, including cholesterol and triglycerides ( Redinbo et al., 2003 ). Interestingly, docking studies revealed that BAs can bind the catalytic site of CES1, with CDCA and TCA having the strongest binding activity ( Kaddurah-Daouk et al., 2018 ). Further mechanistic studies will be required to gain further insight into this CES1-BA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…CES1 mRNA expression level in adipose tissue was positively associated with body mass index (P , 0.001), fasting glucose level (P 5 0.002), insulin (P 5 0.006), and triglycerides (P 5 0.003) (Friedrichsen et al, 2013). Recent studies have also found that CES1 function was positively correlated with increased liver lipid storage and plasma lipid concentrations, indicating that CES1 might be heavily involved in lipid metabolism and is a potential drug target for the treatment of human metabolic disorders (Kaddurah-Daouk et al, 2018;Lian et al, 2018a,b).…”
Section: Disease States Related To Ces1mentioning
confidence: 98%
“…This nucleophile then attacks the carbonyl carbon of the ester substrate, leading to the formation of the acyl-enzyme intermediate, which is stabilized by the oxyanion hole residues Gly142 and Gly143. Additionally, the enzyme has two other ligand-binding sites referred to as the side-door and the Z-site: The side-door serves as an alternative/additional opening to the active site for substrate entrance or as a product release pore: The Z-site probably has an allosteric function by modulation of the binding site accessibility [45,46]. However, the side-door and the Z-site binding sites were not investigated in this study.…”
Section: Resultsmentioning
confidence: 99%